2017
DOI: 10.1249/mss.0000000000001165
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Exertion during Exercise Is Associated with Children's Energy Intake

Abstract: PURPOSE To examine the individual-level factors that predict energy intake (EI) following imposed exercise (EX) and sedentary time (SED) in children. METHODS Healthy-weight children ages 9-12 years (n = 20) reported to the laboratory for 1 baseline and 2 experimental visits (EX and SED) each separated by 1 week in a randomized crossover design. Percent body fat, weight (kg), and height (m) were used to calculate fat-mass index (FM index) and fat-free mass index (FFM index; kg/m2). On the EX day, children exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…Although previous studies have shown in obese adolescent boys and girls (Fearnbach, Silvert, et al, 2016; Thivel, Isacco, et al, 2012; Thivel, et al, 2011) that an acute bout of exercise was able to induce a transient anorexigneic effect by decreasing subsequent food intake, this was only after moderate-to-high intensity exercises, which may explain the present divergent results. Indeed, the two exercise bouts proposed here were set at the individually determined ventilatory threshold, representing about 54.1 ± 5.4 % of VO 2 peak, which is certainly not intensive enough to observe such effects.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Although previous studies have shown in obese adolescent boys and girls (Fearnbach, Silvert, et al, 2016; Thivel, Isacco, et al, 2012; Thivel, et al, 2011) that an acute bout of exercise was able to induce a transient anorexigneic effect by decreasing subsequent food intake, this was only after moderate-to-high intensity exercises, which may explain the present divergent results. Indeed, the two exercise bouts proposed here were set at the individually determined ventilatory threshold, representing about 54.1 ± 5.4 % of VO 2 peak, which is certainly not intensive enough to observe such effects.…”
Section: Discussioncontrasting
confidence: 72%
“…Few studies have been so far methodologically designed to assess relative EI in youth. Recently, Fearnbach and collaborators showed that while a 30-minute cycling exercise (set at 70% VO 2 peak) did not affect subsequent absolute EI in children at risk for obesity, relative EI was significantly lower compared with a rest condition (Fearnbach, Masterson, Schlechter, Ross, et al, 2016). REI was also significantly reduced after 45 minutes of cycling at moderate-to-high intensity in both lean and obese adolescents despite unchanged absolute food consumption in the obese sample (Chaput, Tremblay, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the benefits of physical exercise in reducing hypothalamic inflammation, which might improve WAT browning and its thermogenesis, it is important to highlight that the energy expenditure promoted by practicing physical exercise might often increase energy intake to achieve energy homeostasis. Furthermore, a recent study showed a positive correlation between rate of perceived exertion (RPE) and energy intake in healthy (not obese) children after practicing imposed exercise (Fearnbach et al, 2017 ). However, the effects of physical exercise in reducing energy intake depend on the metabolic status, since several studies are showing that only obese people decrease caloric intake as a consequence of practicing physical exercise practice (Fearnbach et al, 2015 ; Schwartz et al, 2016 ; Thivel et al, 2016 ) (Figure 1 ).…”
Section: Physical Exercise Improves Insulin and Leptin Signaling In Tmentioning
confidence: 99%